PRODUKSI PADI DAN IKAN MAS PADA BERBAGAI PENGELOLAAN AIR, JENIS VARIETAS DAN DOSIS PAKAN IKAN DENGAN SISTEM MINAPADI - Makmur Makmur; Amir Yassi; Edison Saade (Fakultas Pertanian, Universitas Janabadra, 2023)
The aim of the study was to determine water management methods, varieties and doses of fish feed as well as the interactions between the three which resulted in high production of rice plants and carp in the Minapadi system. This research was conducted in Salumokanan Village, Mamasa Regency, West Sulawesi in January - June 2022. The design used was the Split Plot Design with the water management method as the main plot, the type of variety as the child plots and the dosage of carp feed as the children. plot. The water management method (P) as the main plot which consists of 2 levels, namely the wet dry management system / AWD (P1), the flooded irrigation system (P2). Subplots were rice varieties consisting of 2 levels, namely local varieties Mamasa (V1) and Inpari 30 (V2). The sub-plots were the dose of fish feed (D) which consisted of 3 levels, namely 1% fish weight (D1), 3% fish weight (D2) and 5% fish weight (D3). The results of the research on stagnant water management gave the highest yields for the number of productive tillers (12.78 stems), plant dry weight (40.81 g), absolute weight growth (73.06 g), specific growth rate (1.52%) and growth rate survival (94.44%). Wet dry water management yields the highest grain production per plot (8.77 kg). Inpari 30 variety had the best yields on plant dry weight (41.25 g), grain production per plot (8.69 g), absolute weight growth (72.61 g) and specific growth rate (1.51 g). Fish feed dose of 5% yielded the highest number of productive tillers (12.42 g), absolute weight growth (75.76 g) and specific growth rate (1.54%). Intraction of stagnant water management and fish feed dosage of 5% had the best results in absolute weight growth (86.00 g) and specific growth rate (1.63%). The interaction of 30 inpari varieties and 5% fish feed dose gave the best results on the number of productive tillers (13.33 stems), absolute weight growth (84.33 g) and specific growth rate (1.61%). The interaction of stagnant water management, Inpari 30 varieties and fish feed doses of 5% gave the best absolute weight growth (103.33 g) and specific growth rate (1.78%). Keywords: Minapadi, water management, feed dosage.